THE ANALYSIS OF BAHASA INDONESIA TEST QUALITY AT SMA NEGERI 1 MAWASANGKA - Jumriah Jumriah (Universitas Sembilanbelas November Kolaka, 2016)
This study aims to (1) analyze the teacher-made tests so as to obtain an idea of the validity of teacher-made tests bahasa at SMA Negeri 1 Mawasangka, and (2) analyzing teacher-made tests so as to obtain an idea of the reliability of bahasa Indonesia teacher-made tests at SMA Negeri 1 Mawasangka , The method used in this research was analysis method of quantitative paradigm through the approach of evaluation with the object of study was bahasa Indonesia teacher-made tests at SMA Negeri 1 Mawasangka. The data collection was done by using the documentation by taking teacher-made tests that have been used in the midterms. Data were analyzed using product moment to calculate the validity of an essay test and the correlation formula point biserial to calculate the validity of an objective test, Kuder Richardson 20 (KR-20) to calculate the reliability of objective testing, and to calculate the reliability of the test objectives, and to calculate the reliability of the test essays using Cronbach Alpha, while the level of difficulty using the formula of proportion, and the different power using different power index analysis. This study found that: (1) the bahasa Indonesia teacher-made tests at SMA Negeri 1 Mawasangka did not qualify the validity of tests as shown in the results of the analysis of the validity of which 15 items were valid, level of difficulty grains only category of easy and medium, the different power point where 5 grains have the different power, and the persistence of test items that pengecohnya not functioning properly, and (2) the bahasa Indonesia teacher-made tests at SMA Negeri 1 Mawasangka yet did not qualify the reliability of the test as indicated by the results of the analysis of the reliability of the test, both forms of objective tests and test essay form. From the study result, it can be concluded that the bahasa Indonesia teacher-made tests at SMA Negeri 1 Mawasangka did not qualify the validity and reliability of the test was good.